Fabrication of photocurable ferrocene-containing methacrylates polymer for the use of glucose biosensors - Low, Sim Bean; Lee, Yook Heng; Yamin, Bohari; Ahmad, Musa (Penerbit Universiti Sains Malaysia, 2004)
Ferrocene and its derivatives heve been widely used as mediators in the construction of mediated amperometric biosensor. The incorporation of ferrocene-based mediators into polymeric films is always preferred to achieve reagentless devices and also prevent its leaching from the biosensor.